Survival and migration speed of radio-tagged Atlantic salmon ( Salmo salar) smolts in two large rivers: one without and one with dams - Huusko, Riina; Hyvärinen, Pekka; Jaukkuri, Mikko; Mäki-Petäys, Aki; Orell, Panu; Erkinaro, Jaakko (Canadian Journal of Fisheries and Aquatic Sciences, 2018)
Connectivity problems in fish migration in regulated rivers have been widely studied, but few studies have rigorously compared parallel migration success between regulated and free-flowing rivers. Here, survival and migration speed of downstream migrating radio-tagged Atlantic salmon (Salmo salar) smolts were studied in two large neighboring rivers in the northern Baltic Sea area: one without and one with dams. Both rivers have a free-flowing upper section, where the survival and migration speed of salmon smolts were similar. Survival along the lower section of the free-flowing river was about six times higher than in the lower part of the regulated river with five hydropower plants. Migration speed of smolts was also significantly faster in the river without dams. These severe problems in downstream connectivity in the regulated river pose challenging tasks for restoration of salmon populations.